Impact of the COVID-19 Pandemic on the Management of Coral Aquaculture - Alexander Regio Widarto; I Nyoman Dodik Prasetia; Gede Iwan Setiabudi (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
This research aims to determine the impact of the COVID-19 pandemic on coral aquaculture businesses and management strategies in dealing with the pandemic. This research was a quantitative descriptive research. This research used the triangulation method (questionnaire, interview, and observation). This research was conducted at three coral aquaculture companies and a cultured coral transplantation site owned by a private company in Bali. The results showed that the COVID-19 pandemic had a more favorable impact on the coral aquaculture industry, such as the ability to become a source of income for the locals during the pandemic. The difficulties in conducting export activities and restricted mobility were some of the challenges encountered by coral aquaculture businesses during the pandemic. Additionally, the results showed that in order for coral aquaculture businesses to survive the pandemic, management strategies and adaptations are needed.